Immunotherapies for Acute Myeloid Leukemia - Greiner, Jochen (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The efficacy of immunotherapeutic approaches in the treatment of different cancer types is becoming increasingly obvious, and immunotherapies in cancer treatment have experienced a significant breakthrough in the last few years. Immunotherapy encompasses several diverse treatment approaches, each of which has a distinct mechanism of action, and all of which are designed to boost or restore immune function in some manner. Consequently, T cell activating immunotherapeutic approaches like immune checkpoint inhibition, chimeric antigen receptor T cells (CARs), or bi-specific T cell activating antibodies are becoming increasingly important treatment strategies in different solid tumor types as well as in hematological malignancies. T cell responses against malignant cells play a major role in maintaining remission and prolonging overall survival in patients after allogeneic stem cell transplantation and donor lymphocyte infusions (DLI) due to the graft-versus-leukemia effect. In acute myeloid leukemia (AML) after intensive chemotherapy, most patients achieve complete remission; however, the overall survival for all AML patients, especially in elderly patients, is still relatively low. Immunotherapeutic approaches for AML patients might be options to reduce the relapse rate and improve overall survival. This Special Issue will focus on immunotherapeutic approaches in AML in established therapies, like the allogeneic stem cell transplantation including new concepts improving the graft-versus-leukemia effect, but also on new efforts to improve immune responses like adoptive T cell transfer, immune checkpoint inhibition, bi-specific antibodies, and CAR-T-cell approaches.